IMPLEMENTASI PERATURAN DAERAH NOMOR 13 TAHUN 2018 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP UNTUK PEMBANGUNAN BERKELANJUTAN DI KABUPATEN SUMBAWA - Irawansyah, Irawansyah (Nusantara Hasana Journal, 2025)
This study aims to analyze the implementation of the Regional Regulation of Sumbawa Regency Number 13 of 2018 concerning Environmental Protection and Management in supporting sustainable development. This research uses a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation at the Environmental Agency of Sumbawa Regency as the policy implementing institution. The analysis focuses on four policy implementation indicators: communication, resources, implementers' disposition, and bureaucratic structure. The results show that the implementation of the regulation has not been optimal. Communication to the community and across implementing units remains limited. Human resources do not yet fully possess adequate competence, although several employees are certified. The implementers show positive attitudes and strong commitment to carrying out the regulation, yet they are constrained by limited budget availability and insufficient supporting facilities. The bureaucratic structure is clear and well-organized, but responses to public complaints are often slow due to hierarchical bureaucracy. In addition, the main inhibiting factors include limited funding, weak institutional coordination, and inadequate facilities and infrastructure for environmental monitoring. Therefore, increased budget allocation, enhanced human resource capacity, and improved inter-agency coordination are required to achieve sustainable environmental protection.